Severe combined immunodeficiency disease with features of haemophagocytic lymphohistiocytosis: a case report - Mohd Shukri, Nur Diyana; Abd Hamid, Intan Juliana; Mohamad, Norsarwany; Mahayidin, Hasni; Yahya, Nurul Khaiza (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2021)
Severe combined immunodeficiency (SCID) is the foremost extreme frame of primary immunodeficiencies. We described a case report of a 23-month-old boy who presented with pyrexia of unknown origin (PUO) with initial findings suggestive of haemophagocytic lymphohistiocytosis. Physical examination showed unremarkable findings apart from hepatosplenomegaly. The diagnosis of SCID was established from lymphocyte enumeration testing by flow cytometry which revealed a phenotype of T(-), B(-), NK(-) and hypogammaglobulinaemia. The confirmatory genetic test was unable to be performed as the patient’s condition rapidly deteriorated and he succumbed to the illness.